New Conditions for the Existence of Infinitely Many Solutions for a Quasi-Linear Problem. Issue 3 (August 2016) - Faraci, Francesca; Farkas, Csaba
Abstract: In this paper we study a quasi-linear elliptic problem coupled with Dirichlet boundary conditions. We propose a new set of assumptions ensuring the existence of infinitely many solutions.